APPLICATION OF INNOVATIVE ROLLING SYSTEM FOR ROWING ON YAL-6 - Sheichenko T.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to improve the results of athletes in the training process and competitions through the effective use of an innovative rolling system for rowing on YAL-6. Methods and structure of the study. The pedagogical experiment was conducted on the basis of the St. Petersburg state budgetary institution of the sports school of the Olympic reserve "Znamya" among students of the SUAI (Saint-Petersburg State University of Aerospace Instrumentation) and Admiral Makarov SUMIS (Admiral Makarov State University of Maritime and Inland Shipping) in the period from October 2021 to March 2023 in order to evaluate the effectiveness of using the rolling system while moving along the distance. 28 rowers took part in the experiment. Results and conclusions. As part of the experiment, it was revealed that the use of an innovative rolling system for rowing on YAL-6 improves the effectiveness of passing the distance. Athletes involve the entire muscular system of the body in their work, the muscles of the lower limbs of rowers become the main ones when moving in the supporting part of the stroke (wiring).